EPILEPSI REFRAKTER DENGAN GANGGUAN NEUROPSIKIATRI PADA KOMPLEKS TUBEROSKLEROSIS : KASUS JARANG: REFRACTORY EPILEPSY WITH NEUROPSYCHIATRIC DISORDERS IN TUBEROUS SCLEROSIS COMPLEX: A RARE CASE - Yusirizal, Hendra (PERDOSNI, 2025)
ABSTRACT Tuberous Sclerosis Complex (TSC) is an autosomal dominant neurocutaneous syndrome characterized by the development of benign congenital tumors in multiple organs. The incidence of TSC with neuropsychiatric is rare, occurring 1:100,000 to 1:200,000 live births. TSC is associated with epilepsy, autism, and neurodevelopmental disorders. We report a case of 24 yo female patient with seizures of various semiology, since aged 7 months. Seizures and papular lesions nasal region with autism spectrum disorder. The diagnosis was established based on clinical findings, electroencephalography (EEG) showing epileptiform activity in both hemispheres, histopathological of nasal papules supported the diagnosis of TSC, neuroimaging presence of calcified subependymal nodules and multiple cortical tubers. Differential diagnoses including neurofibromatosis and Fahr’s disease were excluded. TSC is caused by mutations chromosome 9q34 (TSC1) or chromosome 16p13 (TSC2). Dysregulated tumor suppressor proteins hamartin and tuberin, which interact with the mTOR protein complex. This disruption leads to dysregulated cell growth and protein synthesis, resulting in the formation of tumors in multiple organs including the brain, where subependymal nodules and cortical tubers are characteristic findings. The diagnosis of TSC is made through clinical evaluation, histopathological examination, EEG, and neuroimaging. Effective management of refractory epilepsy is critical to preventing seizure recurrence and mitigating neurodevelopmental and neuropsychiatric complications. This case multidisciplinary approach in the diagnosis and management of TSC. The appropriate use of anti-seizure medications of refractory epilepsy with TSC can effectively control seizures. Neuropsychiatric disorders managed with behavioral therapy multidisciplinary approach. Keywords: Refractory Epilepsy, TAND, Tuberous Sclerosis Complex